Extrastriate visual cortex reorganizes despite sequential bilateral occipital stroke: implications for vision recovery - Brodtmann, Amy; Puce, Aina; Darby, David; Donnan, Geoffrey (Frontiers in Human Neuroscience, 2015)
The extent of visual cortex reorganization following injury remains controversial. We report serial functional magnetic resonance imaging (fMRI) data from a patient with sequential posterior circulation strokes occurring three weeks apart, compared with data from an age-matched healthy control subject. At 8 days following a left occipital stroke, contralesional visual cortical activation was within expected striate and extrastriate sites, comparable to that seen in controls. Despite a further infarct in the right (previously unaffected hemisphere), there was evolution of visual cortical reorganization progressed. In this patient, there was evidence of utilization of peri-infarct sites (right-sided) and recruitment of new activation sites in extrastriate cortices, including in the lateral middle and inferior temporal lobes. The changes over time corresponded topographically with the patient’s lesion site and its connections. Reorganization of the surviving visual cortex was demonstrated 8 days after the first stroke. Ongoing reorganization in extant cortex was demonstrated at the 6 month scan. We present a summary of mechanisms of recovery following stroke relevant to the visual system. We conclude that mature primary visual cortex displays considerable plasticity and capacity to reorganize, associated with evolution of visual field deficits. We discuss these findings and their implications for therapy within the context of current concepts in visual compensatory and restorative therapies.